2005
DOI: 10.1111/j.1365-2222.2005.02361.x
|View full text |Cite
|
Sign up to set email alerts
|

Wheezing in Chinese schoolchildren: disease severity distribution and management practices, a community‐based study in Hong Kong and Guangzhou

Abstract: SummaryBackground Asthma is a common chronic disease and information on its management practices at the community level is helpful in identifying problems and improving asthma care. Objective To assess the severity status and management of the asthma symptom of wheeze of children at the community level in Hong Kong (HK) and Guangzhou (GZ). Methods Cross-sectional study of children aged 10 years using the International Study of Asthma and Allergic disease in Childhood (ISAAC Phase II protocol). Asthma managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
3
1
3
Order By: Relevance
“…Estudos realizados com adultos e crianças em outros países, como China e França, mostram uma frequência de asma leve intermitente variando de 13 a 83%; de asma leve persistente variando de 11 a 27%; 6 a 36% de asmáticos com doença moderada; e 0 a 25% com doença grave 12,13 . Diferentemente do nosso, a maioria desses estudos considerou o critério de função pulmonar associado aos sintomas para classificar a gravidade da asma.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Estudos realizados com adultos e crianças em outros países, como China e França, mostram uma frequência de asma leve intermitente variando de 13 a 83%; de asma leve persistente variando de 11 a 27%; 6 a 36% de asmáticos com doença moderada; e 0 a 25% com doença grave 12,13 . Diferentemente do nosso, a maioria desses estudos considerou o critério de função pulmonar associado aos sintomas para classificar a gravidade da asma.…”
Section: Discussionunclassified
“…Nosso estudo mostrou uma frequência de asma leve persistente (40%) mais alta que a encontrada em estudos anteriores [12][13][14] . É provável que esse achado possa ser resultante de uma asma inadequadamente tratada, uma vez que os corticoides inalatórios ainda não são amplamente utilizados em populações de baixa renda no Brasil, tais como a que estudamos em Salvador 15 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…12,13 Unlike the present study, however, most of these investigations considered pulmonary function criteria in combination with symptoms for classification of asthma severity. A large population-based study conducted in 29 countries in the Americas, Europe, and Asia estimated asthma severity on the basis of GINA clinical criteria and found that the frequency of severe asthma varied by region, ranging from 11 to 32%.…”
Section: Discussionmentioning
confidence: 58%
“…14 Our study showed mild persistent asthma rates (40%) higher than those reported in the past. [12][13][14] This finding is likely due to inadequate treatment, as inhaled corticosteroids have yet to gain wide use in low-income Brazilian populations, such as this sample of children from Salvador. 15 The present study showed a frequency of severe asthma in the affirmative to questions that used terms other than "wheezing" or "whistling" to refer to symptoms, however.…”
Section: Discussionmentioning
confidence: 83%